2021
DOI: 10.2217/fon-2021-0265
|View full text |Cite
|
Sign up to set email alerts
|

Perceptions of the COVID-19 vaccine Among Patients With Cancer: A Single-Institution Survey

Abstract: Aims: This paper reports the results of a survey assessing the acceptance of the coronavirus disease 2019 (COVID-19) vaccine among patients with cancer. Patients and methods: In total, 111 adult patients with cancer from a single institution were asked to complete a questionnaire designed to assess their knowledge about the vaccine, their readiness to be vaccinated and the determinants of their decision. Results: 61.3% of the patients considered themselves more vulnerable to COVID-19 than the general populatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
31
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(38 citation statements)
references
References 16 publications
(16 reference statements)
5
31
1
Order By: Relevance
“…The multivariate logistic regression analyses indicated that the concern that the COVID-19 vaccine could worsen the prognosis of their cancer treatment was one of the main predictors for vaccine hesitancy ( Table 5 ). These results are similar to data from other countries: in Tunisia, 15.5% cancer patients thought the COVID-19 vaccine could impact cancer treatment outcomes or treatment efficacy [55] ; in the US, among cancer patients who refused to take the COVID-19 vaccine, 56.3% reported being concerned about the compatibility of the COVID-19 vaccine and their cancer treatment [56] .…”
Section: Discussionsupporting
confidence: 84%
“…The multivariate logistic regression analyses indicated that the concern that the COVID-19 vaccine could worsen the prognosis of their cancer treatment was one of the main predictors for vaccine hesitancy ( Table 5 ). These results are similar to data from other countries: in Tunisia, 15.5% cancer patients thought the COVID-19 vaccine could impact cancer treatment outcomes or treatment efficacy [55] ; in the US, among cancer patients who refused to take the COVID-19 vaccine, 56.3% reported being concerned about the compatibility of the COVID-19 vaccine and their cancer treatment [56] .…”
Section: Discussionsupporting
confidence: 84%
“…Previous studies beginning from 2020 reported a positive view of the people for the COVID-19 vaccine in most western countries varying between 59–75% [ 17 , 31–33 ]. A recent study by Mejri et al reported a vaccine acceptance rate of 50.5% from Tunisia, whereas Moujaess et al reported that 55%of the cancer patients inBeirut, Lebanon were ready to be vaccinated [ 34 , 35 ]. Nonetheless, our study that consisted of cancer patients revealed a higher COVID-19 vaccine acceptance (86.7%) than literature.…”
Section: Discussionmentioning
confidence: 99%
“…39 In our experience, patients who, adequately informed, refused vaccination was less than 5%, way less than data in the literature, which report refusal rates over 10%. 40,41 This might be explained by the campaign we held, that involved only professional figures of the Institute, with enrollment via proposal by treating oncologists, also testified by the high level of satisfaction shown by the patients themselves with the vaccination questionnaire.…”
Section: Discussionmentioning
confidence: 99%